Evaluation of mesh-under and route-over routing strategies in AMI systems (2012)
The introduction of smart electric networks is fundamentally based on the integration of the electric grid with an intelligent and bidirectional communications network. As part of such communications network, the metering infrastructure is nowadays being automatized, so that the exchange of traffic between utilities and consumers happens in an efficient way. In this paper, we focus on the problem of routing in advance metering infrastructure (AMI) networks, and perform a qualitative comparison between the mesh-under and route-over routing strategies within the scope of AMI. The specific routing requirements for AMI are identified, and an evaluation of the implications of both routing strategies on those requirements is performed, taking into account issues such as: scalability, end-to-end delay, packet fragmentation, and retransmissions. © 2012 IEEE.